Verification-based software-fault detection - Gladisch, Christoph David (KIT Scientific Publishing, 2011)
Software is used in many safety- and security-critical systems. Software development is, however, an error-prone task. In this work new techniques for the detection of software faults (or software ""bugs"") are described which are based on a formal deductive verification technology. The described techniques take advantage of information obtained during verification and combine verification technology with deductive fault detection and test generation in a very unified way.